The Pharmaceutical literature in Syriac, Greek, and Arabic languages: the case of Hiera of Archigenes (Circe de clásicos y modernos, 2018)
The article traces the role of the Syriac language in the translation’s movement that led to medieval Islamic medicine from the identification of the literary parallels between the recipe of the Hiera of Archigenes of The book of medicines in language Syriac and the Greek and Arab texts that contain testimonies of the same recipe. This recipe which is a compound of varied therapeutic activity is one of the many evidences found that argues in favor of the early work of the Christians of the Syriac language as translators of classical medical texts, preceding those who did it in the Arabic language.
Keywords: Classical tradition; Syriac pharmacy; Arabic pharmacy; The Book of Medicines; Hiera of Archigenes